Optimization of the vibro-impact capsule system - Liu, Yang (Strojniški vestnik, 2016)
Optimization of the vibro-impact capsule system for the best progression is considered in this paper focusing on the choice of the excitation parameters and the shape of the capsule. Firstly, the fastest and the most efficient progressions are obtained through experimental investigations on a novel test bed. Control parameters, the amplitude and the frequency of harmonic excitation, and one of the system parameter, namely the stiffness ratio, are optimized. The experimental results confirm that the control parameters for the fastest progression are not the same as those for the most efficient progression from the energy consumption point of view. Therefore, the capsule system can be controlled either in a speedy mode or in an energy-saving mode depending on the operational requirements. In the second part of the paper, optimization of the capsule shape is studied using computational fluid dynamics (CFD) simulations. Here the aim of achieving the best progression is addressed through minimizing the drag and the lift forces acting on a stationary capsule positioned in the pipe within a fluid flow. The CFD results indicate that both drag and lift forces are dependent on capsule and arc lengths, and finally, an optimized shape of the capsule is obtained.
Keywords: efficiency; eksperimenti; optimizacija; pregled cevi; simulacija CFD; sistem kapsule; učinkovitost; vibroudarec